2009
DOI: 10.1159/000197972
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Self-Reported Knowledge of Genetics and Genetic Education

Abstract: Introduction: Nurses need to use genetic information in care; several areas of current need include primary care, public health, cardiovascular, geriatric and oncology nursing. Nursing faculties may be reluctant to add genetics to existing courses, let alone tackle the work of teaching an entire course in genetics. Objectives: The purpose of this study was to describe the current genetic knowledge of nursing students regarding genetics and genetic education. Methods: This is a self-administered cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 44 publications
(27 reference statements)
0
10
0
1
Order By: Relevance
“…Health professionals presumably are the prime candidates for this endeavor. As health professionals’ knowledge of genetics seems inadequate [36] and research suggests that medical students do not acquire adequate knowledge of genetics during their studies [37], health professionals may need to be educated about genetics first. These issues may tempt us to educate individuals about the underlying principles of genetics only when relevant (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals presumably are the prime candidates for this endeavor. As health professionals’ knowledge of genetics seems inadequate [36] and research suggests that medical students do not acquire adequate knowledge of genetics during their studies [37], health professionals may need to be educated about genetics first. These issues may tempt us to educate individuals about the underlying principles of genetics only when relevant (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring clinical comfort level is an important concept as it relates to level of knowledge (genetic concepts and diseases) and ability to inform patients about the risk of genetic conditions. [15,19,24] …”
Section: Methodsmentioning
confidence: 99%
“…"There is no standard measure of genetic literacy for nurses at any level of education or practice" [8] yet there is a significant gap in nurses' genetic knowledge and ability to integrate that knowledge into practice. [9,10] Studies exploring perceived genetic knowledge and teaching strategies related to the inclusion of genetic content into curricula has been conducted in the United Kingdom; [11,12] New Zealand; [13] Japan; [14] Turkey; [15] Taiwan; [16] and the United States. [7,8,[17][18][19][20][21] These studies revealed that perceived genetic knowledge and clinical comfort remain inadequate among pre-licensure nursing students or advanced practice nursing students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There were 18 dissertations, 2 theses, 20 original research studies, and 4 systematic review articles. Of the 20 original research studies, 6 were from outside the United States including Canada (Bottorff et al, 2005), Spain (Iglesias, Vallejo, Cena, & Fuentez, 2011;Mudd, 2011), China (Hsiao, Van Riper, Lee, Chen, & Lin, 2011), Turkey (Vural, Tomatir, Kurban, & Taspinar, 2009), and Korea (Choi, Jun, Ahn, & Anderson, 2008). Studies that focused on a specific nursing specialty area were not included.…”
Section: Search Outcomementioning
confidence: 99%